Gynecological Care and Contraception Considerations in Women with Cerebral Palsy. Issue 11 (November 2020) - Fasen, Madeline; Saldivar, Brittany; Elamsenthil, Suhane; Thompson, Jordan; Fouad, Lina; Edwards, Linda; Jacob, Rafik
Abstract : Abstract: The purpose of this literature review was to further explore gynecological care and contraceptive use in women with cerebral palsy. We address barriers to pelvic examinations for cervical cancer screenings and current contraceptive methods in severely debilitated patients with cerebral palsy. Abstract : The purpose of this literature review was to further explore gynecological care and contraceptive use in women with cerebral palsy. The article addresses barriers to pelvic examinations for cervical cancer screenings and current contraceptive methods in severely debilitated patients with cerebral palsy.